Recurring febrile illness in a slaughterhouse worker. Issue 902 (1st December 2000) - Ganeshram, K N; Ross, A; Cowell, R P W; Cefai, C; Woodward, M J
Abstract : A slaughterhouse worker presented with fever and a pleuropericardial effusion. Conventional microbiology failed to identify the responsible organism. However, DNA sequencing definitively identified Campylobacter fetus ssp fetus, which is rare in immunocompetent individuals. Prolonged treatment was required to eradicate the infection.